Penerapan Model Pembelajaran Berbasis Proyek untuk Meningkatkan Aktivitas dan Keterampilan Analisis Sastra - Sovia Wulandari; Liza Septa Wilyanti (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2023)
Abstract The purpose of this study was to improve literary analysis activities and skills using a project-based learning model in the Indonesian Literature study program, Faculty of Teacher Training and Education, Jambi University. The method used in this research is Classroom Action Research (PTK) which was carried out in two cycles in the Oral Literature Study course. In the first cycle, two meetings were held and the second cycle was held three meetings. Each cycle is carried out in the stages of planning, implementation, observation, and reflection. The data were analyzed in accordance with the predetermined assessment rubric. In the first cycle, the students' activity scores increased, 80% of which reached the good category score and 20% reached the very good category score compared to the activity scores obtained in the pre-cycle. As for the value of the results of literary analysis in cycle I, it has not yet reached the target, namely not exceeding 50% of students getting good and very good category scores. In cycle II, the value of activity and the results of literary analysis experienced a significant increase, namely 100% of students getting very good category scores for activity scores and 80% of students getting good scores and 20% getting very good scores for the results of literary analysis. Based on these values, it can be said that the application of the Project Based Learning learning model in the Oral Literature Study course to improve activities and oral literature analysis skills is appropriate and effective to be applied. Keywords: Activity, Skill, Literature Analysis, PjBL